Effect of Cognitive Abilities, Emotional Intelligence and Self Esteem on Investment Decision Making: A Prospect Theory Approach - Arora, Muskaan (My University, 2016)
The most important aspect of investment decision making is stock market participation. Various studies have robustly supported that psychological (cognitive ability, emotional intelligence and self-esteem) and demographic (age and gender) factors influence behavioral biases, stock market participation and risk preference of the investors. However, previous studies have generally been unable to shed much light on the mechanisms through which psychological and demographic factors affect investment decision making. Therefore, a mediational analysis was considered to investigate whether behavioral biases (loss aversion and regret) and risk preferences act as a linkage between cognitive ability, emotional intelligence, self-esteem and stock market participation and also between age, gender and stock market participation of the investors. A total of 740 investors (graduate and above) out of which 534 were males and 206 females of the two age groups 25-40 and 41-55 years with average annual income of Rs. 3,00,000- 9,60,000 from northern part of India participated in the study. Loss aversion was measured by lottery choice task experiment and the level of regret was measured by providing regret inducing situation followed by decision regret scale. The extent of stocks market participation and risk preferences of the individuals were assessed by using a questionnaire seeking investment related information. A conceptual framework was formulated and tested using AMOS 21. It was found that individuals with low cognitive abilities, low emotional intelligence and low self esteem show more loss aversion and regret and prefer fewer stocks and less risk in their investments as compared to individuals with high cognitive abilities, high emotional intelligence and high self-esteem. Individuals in the age group 41-55 years show more loss aversion and regret, and also they participate more in stocks and prefer to take fewer riskss in their investments as compared to individuals with age group 25-40 years. Similarly, females show more loss aversion and regret, and also participate less in stocks and prefer to take fewer riskss in their investments as compared to males. In addition to this, it was also found that loss aversion, regret and risk preferences act as mediating variable between psychological (cognitive ability, emotional intelligence and self-esteem), demographic (age and gender) and stock market participation of the investors. The present study advances previous findings by demonstrating that variation in behavioral biases and risk preferences play an important role in mediating the associations between psychological and demographic factors and stock market participation of the investors.
Keywords: Behavioral finance; cognirive ability; emotional intelligence; Self esteem; stock market participation